Structural systematics of RSn(S2CNR0R00)2Cl compounds - Muthalib, A.F.A.; Baba, I.; Khaledi, H.; Ali, H.M.; Tiekink, Edward R.T. (Oldenbourg Verlag, 2014)
Three new organotin(IV) structures of general formula RSn(S2CNR0R00)2Cl, where R0 6¼ R00, namely MeSn $ [S2CN(Me)(Cy)]2Cl (1), MeSn[S2CN(i-Pr)(CH2Ph)]2Cl (2) and PhSn[S2CN(Et)(i-Pr)]2Cl (3) are described. Each structure features tin in a distorted octahedral geometry defined by a CClS4 donor set as a result of two chelating dithiocarbamate ligands. In all cases the tin-bound carbon and chloride atoms are cis. The shorter Sn–S bond lengths in 3 are correlated with the presence of the relatively more electronegative Sn-bound phenyl substituent. The new structures conform to the structural motif adopted by all other compounds with the formula RSn(S2CNR0R00)2Cl, where R0 ¼ R00, suggesting the unsymmetrical substitution pattern of the dithiocarbamate ligands in the present study does not influence the adoption of this structural motif. The homogeneity in the structural motif notwithstanding, non-systematic variations in geometric parameters are found in these structures indicating an overall influence of crystal packing upon molecular geometry.